Short-Term Rental Bans and Housing Prices: Quasi-Experimental Evidence from Lisbon - Duarte Gonçalves; Susana Peralta; Jo\~ao Pereira dos Santos (Institute of Labor Economics (IZA), 2022)
We estimate the causal impact of a 2018 zoning reform that banned new short-term rental registries in some parts of Lisbon. The short-term rental licence expires when the house is sold, hence the ban removes the option value of short-term renting a property. We rely on two administrative data sets on short-term rental registries and real estate transactions, complemented with Airbnb data on listings and prices. We employ a difference-in-differences estimation taking advantage of the spatial discontinuity in the ban. We document a spike in newly registered housing units, between the announcement and the implementation of the ban. The reform decreases real estate prices by 8%, mostly in two-bedroom dwellings, for which the price drops 20%. We conclude that heterogeneous effects are key to understanding the backlash against short-term rentals.
Keywords: R12; R21; R30; 330; Airbnb; policy analysis; housing market; short-term rental; Portugal